Preceding vowel duration as a cue for voicing - C.S, Sujatha (Journal of All India Institute of Speech and Hearing)
Speech perception in children is an area of focus in the past 2 decades. The presence of developmental trends in children perception has triggered several studies in this area using various cues to perception. Variation in adult perceptions across different languages has necessitated the study of speech perception in children from different linguistic backgrounds.